Exploring card sort methods: Interaction and implementation for research, education, and practice. Issue 1 (18th October 2019) - Conrad, Lettie Y.; Demasson, Andrew; Gorichanaz, Tim; VanScoy, Amy
ABSTRACT: Exploring research methods can help scholars and professionals accurately answer questions and solve problems. Card sorting, which encompasses a variety of methods aimed at understanding participants' subjectivities, is not commonly used in information science research. This panel will familiarize attendees with the purpose and procedures of card sort methods and to allow for hands‐on interaction with the artifacts and software using examples from different techniques. The opportunity to interact with the tools of card sorting methods will help to familiarize the method and allow them to better evaluate it for their research needs. Using a simple PowerPoint application, participants will have a chance to see how card sorting works as a reflective activity without significant expense or effort. Panelists, who have used these methods in industry and research, can discuss specific research questions with attendees and offer advice.